Atrial fibrillation and heart failure- results of the CASTLE-AF trial - Syed Raza Shah; Palwasha Ghulam Moosa; Mazia Fatima; Rohan Kumar Ochani; Waqas Shahnawaz; Muhammad Ahmed Jangda; Syed Arbab Shah (Greater Baltimore Medical Center, 2018)
Congestive Heart Failure (HF) and Atrial Fibrillation (AFIB) often coexist. Catheter ablation is a well-established option for symptomatic AFIB that is resistant to drug therapy in patients with otherwise normal cardiac function. This has been seen in various studies where catheter ablation was associated with positive outcomes in patients with HF. Recently, the study results from the Catheter Ablation versus Standard Conventional Therapy in Patients with Left Ventricular Dysfunction and Atrial Fibrillation (CASTLE-AF) trial were published. After a median follow-up of more than 3 years, patients getting catheter ablation for AFIB had significantly fewer hospital admissions as well as death from worsening HF. In addition, 63% of patients in the ablation group were in sinus rhythm, as compared with 22% of those in the medical-therapy group (P < 0.001). This trial may represent a significant additional therapeutic tool in the clinical prevention and management of cardiovascular mortality and morbidity. While catheter ablation does not eliminate the AFIB per se, it can limit the ventricular rate by eliminating triggers and altering electrophysiological connections in the heart in a similar fashion to rate control anti-arrhythmic drugs. Longer-duration normal sinus rhythm may improve outcomes by means of a number of mechanisms, including greater atrial emptying, all of which translate into improved cardiac output. A better understanding is needed as to why a decrease in density, but not complete elimination of atrial fibrillation, is sufficient for reverse remodelling. It is anticipated that the results of the CASTLE-AF trial will soon be implemented in international guidelines.